2020
DOI: 10.3389/fphar.2020.594744
|View full text |Cite
|
Sign up to set email alerts
|

N-Butanol Fraction of Wenxia Formula Extract Inhibits the Growth and Invasion of Non-Small Cell Lung Cancer by Down-Regulating Sp1-Mediated MMP2 Expression

Abstract: Lung cancer is the most commonly diagnosed cancer and the leading cause of cancer death. It is necessary to develop effective anti-lung cancer therapeutics. Wenxia Formula (WXF), an empirical traditional Chinese herbal formula, has been reported to have significant antitumor activity. In this study, to further clarify the material basis of the anti-tumor effect of WXF, we investigated the cytotoxic effect of the N-butanol fraction of Wenxia Formula extract (NWXF) against two lung cancer and one normal human ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It also, can activate MMP-9, MMP-3, and MMP-2 and help to grow and expand cancer cells ( 37 38 ). Plant-based natural substances detract the expression of MMP-2 MMP-9 in tumour cells ( 39 40 ). Recent studies have shown that taraxasterol reduced MMP-2 and MMP-9 levels in thyroid and gastric cancers ( 41 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also, can activate MMP-9, MMP-3, and MMP-2 and help to grow and expand cancer cells ( 37 38 ). Plant-based natural substances detract the expression of MMP-2 MMP-9 in tumour cells ( 39 40 ). Recent studies have shown that taraxasterol reduced MMP-2 and MMP-9 levels in thyroid and gastric cancers ( 41 42 ).…”
Section: Discussionmentioning
confidence: 99%